L’alternance -ar/-ear en morphologie verbale espagnole : Quelques exemples d’analyse au prisme de la cognématique et de la chronomorphogénèse (Signifiances (Signifying), 2021)
Our paper presents a submorphological analysis of the verbal alternation -ar/-ear considering on the one hand the cognematic approach elaborated by D. Bottineau and on the other hand the chronomorphogenesis theory developped by Y. Macchi. The contrast between the verbal forms -ar and -ear will allow us to isolate the vowel E in order to examine the morphophonological and semantical impact that E could have in this verbal paired.